Somatotopical characteristics of chronic prostatitis patients - Yu. Yu. Vinnik; J. V. Кaracheva; A. S. Maximov (Сеченовский вестник, 2016)
The anthropometric study of men in the ﬁrst nature age (28± found more frequent asthenic (27,1%) and endomorph (29,4%) somatotypes in chronic prostatitis patients compared to general population. Consequently, the endomorphic and asthenic young men are at risk for chronic prostatitis and these ﬁndings may be used in clinical practice.